1998
DOI: 10.1097/00002030-199813000-00007
|View full text |Cite
|
Sign up to set email alerts
|

HIV protease genotype and viral sensitivity to HIV protease inhibitors following saquinavir therapy

Abstract: Recruitment of Val-48/Met-90 mutations was not found to be synonymous with cross-resistance. Indeed, the majority of isolates with these mutations retained sensitivity to at least one protease inhibitor (Val-48, 86%; Met-90, 77%). The recruitment of accessory mutations may occur only after the selection of key resistance mutations. Furthermore, Met-90 was found to be a poor marker of cross-resistance in SQV-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…Subsequently, isolates from patients began to show mutations in the protease gene that correlated directly to in vivo resistance not only to indinavir but also to a diverse panel of HIV-1 protease inhibitors (6). In similar fashions, cross-resistance was also observed for viral isolates from patients treated with other inhibitors (7)(8)(9)(10)(11).…”
Section: Resultsmentioning
confidence: 61%
“…Subsequently, isolates from patients began to show mutations in the protease gene that correlated directly to in vivo resistance not only to indinavir but also to a diverse panel of HIV-1 protease inhibitors (6). In similar fashions, cross-resistance was also observed for viral isolates from patients treated with other inhibitors (7)(8)(9)(10)(11).…”
Section: Resultsmentioning
confidence: 61%
“…In the United States and Europe, about 10% of new infections are with HIV-1 strains harboring resistance to at least one of three classes of anti-HIV drugs (16,23,30,93,144,233,234,317,357,372,384,416 [61][62]1999) (Table 3). …”
Section: Evolution Of Hiv-1 Drug Resistancementioning
confidence: 99%
“…The spectrum of mutations developing during therapy with indinavir, nelfinavir, saquinavir, and ritonavir have been well characterized (9,24,54,61,265,281,320,334), but fewer data are available for amprenavir (237a) and lopinavir (35). The dynamic susceptibility range for indinavir, ritonavir, saquinavir, nelfinavir, and lopinavir is about 100-fold in most drug susceptibility assays (148,149,290,393; Brun, S., D. Kempf, J. Isaacson, A. Molla, H. Mo, C. Benson, and E. Sun, abstract 452, 8th Conference on Retroviruses and Opportunistic Infections, Chicago, Ill., 2001).…”
Section: Pismentioning
confidence: 99%
“…Assay results along with the mutational makeup of each isolate tested are summarized in Table 1. Sequence analysis of the HIV-1 RF variants selected in cell culture by IDV, NFV, and RTV revealed that the Prt substitutions present were mostly representative of those identified in clinical trials (1,4,5,6,26,33,38). However, the resistant RF strain selected with APV contained only the mutation V82I Table 1 showed that both the clinical and laboratory IDV-resistant isolates (15-and 24-fold decreases in sensitivity to IDV, respectively) displayed 6-to 9-fold resistance to BMS-232632, NFV, and SQV.…”
Section: Bms-232632 Susceptibilities Of Hiv-1 Strains Resistant To Cumentioning
confidence: 99%
“…The current group of Prt inhibitors select for distinct but overlapping sets of amino acid substitutions within the Prt molecule. The key signature substitutions for IDV and RTV resistance reside at amino acid residues V82, I84, or L90, those for SQV resistance reside at G48, I84, or L90, those for NFV resistance reside at D30 or L90, and those for APV resistance reside at I50 or I84 (1,4,5,6,7,10,11,15,16,22,23,26,30,32,33,36,38; M. Tisdale, R. E. Myers, M. Al T-Khaled, and W. Snowden, 6th Conf. Retrovir.…”
mentioning
confidence: 99%